Successful PhD anyone? - Ng, Siew Imm; Tee, Keng Kok; Ho, Jo Ann; Zawawi, Dahlia; Jantan, Amer Hamzah (Universiti Putra Malaysia Press, 2019)
When we first wrote Ph.D anyone?, we were motivated by the desire to share our own Ph.D. experiences with you. Our first version, Ph.D anyone? Was based on essential topics for doctoral students, topics that we considered as important survival skills needed as a Ph.D student. We were pleased to hear from our readers how our book had helped them in their own Ph.D journey and how much it had impacted them. Motivated by the acceptance of our first book, we decided to embark on this second book, Successful Ph.D, Anyone? Showcases five completion stories of our own students; their difficulties, joys and how they succeeded in their Ph.D journeys. We felt it was essential to have our students share their experiences to inspire readers so that they know the Ph.D is not an impossible journey, if we have the right attitude, motivation and strategies. As you read each chapter, you will probably get a sense of the hard work, sacrifices and challenges encountered during each student’s journey. Having said that, each of them graduated and have gone on to become successful people in their own chosen fields. Our students who have written their experiences consist of two full-time Ph.D students, a working adult and two international students. These students were carefully chosen for their diverse experiences; for we believe no two Ph.D journeys are ever alike. We started each chapter with the student’s experiences which is followed by our observations as their supervisors.